MATHEMATICAL MODELING OF CHANGES DAILY TRAFFIC VOLUME - E. Pechatnova (Вестник СибАДИ)
The problem of taking into account traffic density fluctuations. Based on the analysis of actual traffic intensity values of the mathematical model in the form of a functional relationship, taking into account the month of the year, day of week and time of day. In addition, in the simulation takes into account the different intensity distribution in the different days of the week, holidays and pre-holidays. The evaluation of the adequacy of the model and its comparison with existing methods, which showed that the proposed relationship can be used to calculate the intensity at any given time.